Training In Writing of Scientific Articles Based on Item Analysis Research (Universitas Negeri Semarang, 2022)
Writing scientific articles is one of the activities a teacher must carry out in the context of Continuous Professional Development and promotion. The purpose of this Community Service activity is to provide training on writing scientific articles based on item analysis research for teachers at Madrasah Tsanawiyah Tarbiyatul Banin. The main priority of the needs of partners in the school is to provide knowledge and skills to teachers in converting the results of item analysis research that teachers have carried out into scientific articles. The agreement between MTs Tarbiyatul Banin partners and the service team is to conduct training in the writing of scientific articles. The training was conducted using a workshop approach consisting of the lecture method to teach teachers about the types of scientific publications for promotion, complete scientific article frameworks, and applicable methods. It improves teacher skills in compiling scientific articles based on item analysis research and assignments and assists in preparing scientific articles worthy of publication in national scientific journals. The results of this community service show that teachers who participate in the training are satisfied and motivated to compile scientific articles. Penyusunan artikel ilmiah merupakan salah satu kegiatan yang wajib dilakukan oleh seorang guru dalam rangka Pengembangan Keprofesian Berkelanjutan dan untuk kenaikan pangkat. Tujuan kegiatan Pengabdian kepada Masyarakat ini adalah memberikan pelatihan tentang penyusunan artikel ilmiah berbasis penelitian analisis butir soal pada guru di Madrasah Tsanawiyah Tarbiyatul Banin. Prioritas utama dari kebutuhan mitra di sekolah tersebut adalah memberikan pengetahuan dan keterampilan kepada guru dalam mengubah hasil penelitian analisis butir soal yang sudah dilakukan oleh guru ke dalam bentuk artikel ilmiah. Kesepakatan antara mitra MTs Tarbiyatul Banin dan tim pengabdian adalah melakukan pelatihan penyusunan artikel ilmiah. Pelatihan dilakukan menggunakan pendekatan workshop yang terdiri dari metode ceramah untuk memberikan pengetahuan kepada guru mengenai jenis-jenis publikasi ilmiah untuk kenaikan pangkat, kerangka artikel ilmiah secara lengkap, metode aplikatif untuk meningkatkan keterampilan guru dalam menyusun artikel ilmiah berbasis penelitian analisis butir soal, serta penugasan dan pendampingan penyusunan artikel ilmiah yang layak publikasi di jurnal ilmiah nasional. Hasil dari pengabdian masyarakat ini menunjukkan bahwa guru yang mengikuti pelatihan merasa puas dan termotivasi dalam menyusun artikel ilmiah.